A study on correlation of placenta praevia with previous caesarean section and other risk factors - Kaul, Somika; Mir, Shahida (International Journal of Research in Medical Sciences, 2019)
Background: Obstetric haemorrhage is the leading cause of preventable maternal mortality worldwide. One of the major contributors to obstetric haemorrhage is antepartum haemorrhage which is mainly caused by placenta praevia and abruptio placenta. The study aims to quantify the risk of placenta praevia based on the presence and number of caesarean sections and to assess other risk factors. Methods: This study was a prospective case control study conducted in the department of obstetrics and gynecology, Lalla Ded hospital, Srinagar, Jammu and Kashmir, India from August 2009 to October 2010. As per the inclusion and exclusion criteria of study 100 cases and 200 controls were selected and the association of placenta praevia with proposed risk factors was analysed statistically. Results: Present study showed that the risk of developing placenta praevia in future pregnancy increased steadily as the number of previous caesarean sections increased, risk being 2.1, 2.8 and 4 times with previous one, two and three caesarean deliveries respectively. Similarly, the risk of developing placenta praevia was more in women with history of previous abortion (risk being 2.8 and 6.5 times more in women with one and two abortions in the past). Previous dilatation and curettage and age more than 30 years also proved to be independent risk factors. Conclusions: To conclude advanced maternal age, previous abortion, dilatation and curettage and a history of previous caesarean section appear to increase the occurrence of placenta praevia. The study strongly emphasises the need to decrease the primary caesarean section rate.